Aberrations in the microbiome of cyanobacteria from a tropical estuary polluted by heavy metals. (November 2020) - Jasmin, C.; Anas, Abdulaziz; Singh, Dharmesh; Purohit, Hemant J.; Gireeshkumar, T.R.; Nair, Shanta
Abstract: The effect of heavy metal pollution on the microbiome of cyanobacteria in Cochin estuary (CE) on the southwest coast of India is reported in the study. Statistically significant difference in heavy metal concentration was observed between water, suspended particulate matter (SPM) and sediment. The Zn, Cd, Cu, Ni and Cr were 2–6 times higher in the SPM compared with the sediment, while Pb was 10 to 25 times higher. Although nearly 60% of the species diversity of microbiome was common between cyanobacteria enriched from the upstream (S1S) and downstream (S11B), there was a difference in the major groups of heterotrophic bacterial associates. Proteobacteria was the dominant phylum (>80%) in S1S, while it was second only (27.5%) after Planctomycetes (37.4%) in S11B. The results of the current study indicate that the pollution can influence an ecosystem at the micro-niche level. Highlights: Microbiome supports adaptation of cyanobacteria to environment. Particulate matter was the major reservoir of heavy metal accumulation in the estuary. Heavy metal pollution alters the microbiome of Cyanobacteria. γ-Proteobacteria are dominant in Synechocystis sp. from polluted waters.